Compétences linguistiques et culturelles des organisations de santé. Analyse critique de la littérature - Aucoin, Léonard (InfoVeille Santé, 2008)

L’accès aux soins de santé pour les communautés minoritaires de langue officielle : fondements juridiques, initiatives actuelles et perspectives d’avenir - Bélanger, Mauril; Comité permanent des langues officielles (Gouvernement du Canada, Chambre des communes, 2003)

Poids, santé générale et santé mentale : la situation de divers sous-groupes d'immigrants au Canada - Bergeron, Pascale; Auger, Nathalie; Hamel, Denis (Revue canadienne de santé publique, 2009)
Contexte Au Canada, l’immigrant récent est souvent en meilleure santé que le non-immigrant. L’état de santé des sous-groupes d’immigrants (ethniques, culturels, linguistiques) est moins bien connu. Méthode En utilisant des données de l’Enquête sur la santé dans les collectivités canadiennes 2005 (Cycle 3.1), les associations entre trois caractéristiques des immigrants (1-temps écoulé depuis l’immigration, 2-être une minorité visible, 3-parler une langue officielle) et trois indicateurs de santé (1-santé générale perçue, 2-santé mentale perçue, 3-indice de masse corporelle (IMC)) ont été modélisées à l’aide de régressions logistiques multiples pour les immigrants des régions métropolitaines de recensement de Montréal, Toronto et Vancouver. Elles ont été ajustées pour des facteurs sociodémographiques. Résultats Les immigrants récemment arrivés qui appartiennent à une minorité visible sont moins susceptibles d’avoir une mauvaise santé perçue, tant générale (RC 0,72; IC95 % 0,54–0,97) que mentale (RC 0,64; IC95 % 0,43–0,96) et un IMC≥25 (RC 0,51; IC95 % 0,43–0,61) que les non-immigrants. Ceux qui n’appartiennent pas à une minorité visible ne présentent pas ces associations. Les immigrants qui ne parlent pas une langue officielle sont plus susceptibles d’avoir une mauvaise santé générale perçue (RC 1,49; IC95 % 1,06–2,10) que les non-immigrants. À Toronto et Vancouver, les immigrants tendent à être associés à un IMC moindre que les non-immigrants alors que ce n’est pas le cas à Montréal. Conclusion Cette étude témoigne de la présence du phénomène de l’immigrant en bonne santé au Canada mais démontre qu’une grande variabilité existe entre les sous-groupes d’immigrants. Ces constats sont importants pour une planification adéquate des services aux immigrants.

La santé en francophonie canadienne : vivre en situation minoritaire influence-t-il la santé ? - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène (Bulletin de l’association des médecins de langue française, 2009)
La littérature suggère l'hypothèse d'une santé différentielle des francophones en situation minoritaire au Canada. L'effet de minorité sur la santé perçue a été mesuré à l'aide des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) de 2001 et 2003. Une analyse de régression logistique multivariée séquentielle montre que les francophones minoritaires – hommes et femmes – sont plus enclins à déclarer une moins bonne santé que les anglophones majoritaires. Contrairement aux femmes, cette disparité chez les hommes demeure significative même lorsque nous ajustons pour certains grands déterminants de la santé. L'étude illustre que l'action des déterminants de santé peut être ainsi modulée par le rapport minoritaire/majoritaire. Les inégalités ainsi révélées appellent à une réflexion sur les politiques d'accès linguistique aux soins de santé.

Health profile of English-speaking minority communities in Quebec [infographic] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)

Profil santé des communautés anglophones minoritaires au Québec [infographie] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H. et Gagnon-Arpin, I. (2009). Profil santé des communautés anglophones minoritaires au Québec [infographie]. Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada (RISF). Santé Canada. fs-code-orig: Bouchard-2009e

La santé en situation linguistique minoritaire - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gilbert, A.; Dubois, L. (Politiques de Santé, 2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H., Gilbert, A. et Dubois, L. (2009). La santé en situation linguistique minoritaire. Politiques de Santé, 4(4), 36-42. https://www.ncbi.nlm.nih.gov/pmc/Article de revue s/PMC2700700/pdf/policy-04-036.pdf fs-code-orig: Bouchard-2009a

The vitality of the English-speaking communities of Quebec: From community decline to revival - Bourhis, Richard Y. (Centre d’études ethniques des universités montréalaises, Université de Montréal, 2008)

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Programme de contribution pour l'amélioration de l'accès aux services de santé pour les communautés de langue officielle en situation minoritaire. Évaluation formative. - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Pour un nouveau leadership en matière d'amélioration des services de santé en français. Rapport au ministre fédéral de la santé - Comité consultatif des communautés francophones en situation minoritaire (Santé Canada, 2007)

Société, langue et santé : les barrières à l'accès aux services de santé pour les communautés francophones minoritaires - Consortium national de formation en santé (Santé Canada, 2008)

Towards a new leadership for the improvement of health services in French. Report to the federal minister of health - Consultative Committee for French-Speaking Minority Communities (Health Canada, 2007)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Le démarrage d'un programme national de recherche sur la santé des communautés francophones minoritaires - une initiative du Consortium national de formation en santé - Desbiens, Francine (Reflets, 2005)

De l’émergence à la consolidation. L’état de santé des francophones en situation minoritaire - Forgues, Éric; Guignard Noël, Josée; Nkolo, Christiane; Boudreau, Jonthan (Consortium national de formation en santé et Institut canadien de recherche sur les minorités linguistiques, 2009)

Aperçu des comportements de santé en lien avec l’image corporelle des adolescentes francophones vivant en milieu minoritaire - Gérome, Marie-Hélène (Reflets, 2001)

L’environnement et la vitalité communautaire des minorités francophones : vers un modèle conceptuel - Gilbert, Anne; Langlois, André; Landry, Rodrigue; Aunger, Edmund (Francophonies d'Amérique, 2005)

Community involvement of seniors in the Eastern Townships - Gosselin, Chedly; Viens, Caroline (Journal of Eastern Townships Studies, 2006)
This paper explores Anglophone seniors' participation within the community of the Estrie region of Quebec. A healthy relationship between Anglophone and Francophone communities improves access to state health and social services and relieves the social isolation of those living in rural areas. Immigrant migration to the area as well as out-migration of young Anglophones is profoundly affecting the delivery of health and social services as well as changing family, community, nation, culture and what it means to be a citizen.

Protocole d’évaluation de la sécurité à domicile (PESAD) : version francophone du SAFER-HOME v.3 - Hébert, Michèle; Brasset-Latulippe, Anne; Bourgault-Côté, Sylvianne; Meilleur, Valérie; Chiu, Teresa (Francophonies d'Amérique, 2009)
Les intervenants de la santé sont appelés à se prononcer sur la sécurité des aînés vivant à domicile et ils ont, à cet effet, très peu d’outils francophones à leur disposition. Le Protocole d’évaluation de la sécurité à domicile (PESAD) est issu de la traduction et de la validation transculturelle du SAFER-HOME. Le processus de validation et l’étude de la fidélité des résultats ont mis en lumière un outil intéressant et possédant de bonnes qualités métrologiques. Il permet aux intervenants francophones d’obtenir des résultats d’évaluation complets et rigoureux relativement à la sécurité à domicile des aînés francophones.

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

Sources de données de Statistique Canada sur les minorités de langue officielle (n°91-549-X-n°001) - Lafrenière, Sylvie (Statistique Canada, 2009)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°001) - Lafrenière, Sylvie (Statistics Canada, 2009)

Autodétermination du comportement langagier en milieu minoritaire : un modèle conceptuel - Lagacé, Josée; Lefebvre, Pascal (Francophonies d’Amérique, 2005)

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Rapport de l’évaluation sommative du Projet de formation et de recherche du Consortium national de formation en santé - LeBlanc, Pierre (Conseillers en gestion PRAXIS, 2008)

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)
fs-ref-orig: Official Language Community Development Bureau. (2007). Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. Health Canada. fs-code-orig: Official Language Community Development Bureau-2007

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

Language proficiency, gender and self-reported health: An analysis of the first two waves of the longitudinal survey of immigrants to Canada - Pottie, Kevin; Ng, Edward; Spitzer, Denise; Mohammed, Alia; Glazier, Richard (Canadian Journal of Public Health, 2008)
Background Most immigrants to Canada now come from Asia, the Middle East, the Caribbean and Africa, where cultures and languages often differ significantly from the Canadian context. Subgroups of immigrants experience disparities in health. Inability to communicate in an official language in Canada may be a marker of risk for poor health due to both pre- and post-migration factors. We aimed to study the relationship between language proficiency and self-reported health. Methods We conducted a cross-sectional analysis of the first two surveys of the Longitudinal Survey of Immigrants to Canada (2001, 2003), a population-based cohort study of new immigrants to Canada. Specifically, we used logistic regression analyses to examine the relationship between self-reported health and language proficiency by sex, controlling for a range of health determinants at 6 months (wave 1) and 2 years (wave 2) after arrival. Results After controlling for covariates (age, sex, education, region of birth, immigrant class, job satisfaction, access to health care), analysis of the wave 1 survey showed that poor proficiency in English or French is significantly related to the self-reported poor health (OR=2.0, p<0.01). And this relationship was consistent in the wave 2 survey (OR=1.9, p<0.01). We also found that this statistically significant association between poor language proficiency and self-reported health holds only for women (wave 1 survey OR=2.6, p <0.01, wave 2 survey OR=2.2, p<0.01), not for men. Conclusion The association between poor language proficiency and poor self-reported health, and particularly its significantly greater impact on women, has implications for language training, health care and social services, and health information.

The network’s approaches for the maintenance and creation of primary health services in English for the Quebec City region - Sanderson, Duncan; Grégoire, Louise; Reinharz, Daniel (Agence de la santé et des services sociaux de la Capitale-Nationale & Direction régionale de santé publique, 2006)
fs-ref-orig: Sanderson, D., Grégoire, L., & Reinharz, D. (2006). The network’s approaches for the maintenance and creation of primary health services in English for the Quebec City region. Agence de la santé et des services sociaux de la Capitale-Nationale & Direction régionale de santé publique. fs-code-orig: Sanderson-2006

Culture, language and self- assesments of future health: Anglophones and Francophones in Quebec’s Eastern Townships - Stout, Dale; Charpentier, Claude; Chiasson, Myriam; Filion, Emmalie (Journal of Eastern Townships Studies, 2009)
This study examines subjective ratings of health (SRH) by Francophones and Anglophones living in the Eastern Townships. Global self-ratings of health are regarded as sensitive predictors of future health states, mortality, functional decline and disability, and utilization of the health-care system. Yet despite their pragmatic value, SRH are poorly understood. Along with a spontaneous monitoring of present health states, culture and language are listed as determinants of SRH. Few studies exist, however, that clearly delineate the direction and degree of effect that culture and language have on SRH. Adopting a temporal assessment of SRH, we asked 358 Anglophones (N=176) and Francophones (N=171) from the Eastern Townships, aged 18 to 95, to rate their health in the past, present, and future. To isolate culture and language effects we also asked participants to rate their future health if they “remained in Quebec”. Results revealed a significant interaction between age and temporal ratings of health (SRH). Turning to the effects of location (unspecified or “in Quebec”) on future health ratings, there was a significant interaction with language. Post hoc tests revealed no significant differences in Francophones’ future health ratings (unspecified or “in Quebec”) but a significant ratings drop was noted for Anglophones if they “remained in Quebec”. After controlling for bilingualism, this interaction remained statistically significant.

The effects of age and culture on subjective well-being: A case study in the Eastern Townships - Stout, Dale; Filion, Emmalie; Chiasson, Myriam; de Man, Anton; Charpentier, Claude; Pope, Megan (Journal of Eastern Townships Studies, 2008)
The present study of diachronous ratings of subjective well-being (SWB) was modeled on research undertaken by Staudinger, Bluck & Herzberg (2003). In addition, we were interested in determining the effects of culture and context (where one lives) on SWB ratings. To gage these effects, we included the factor of mother tongue and altered the Life Satisfaction Questionnaire by adding a question concerning expected well-being in Quebec. We asked 350 Anglophones and Francophones from the Eastern Townships, aged 18 to 95, to rate their SWB in the past, present, future, and future ‘in Quebec’. The results concerning the effects of chronological age on diachronistic SWB ratings followed the patterns of previous research: young people (aged 18–38) rate past SWB lower than present SWB and future SWB much higher; middle-aged people (aged 39–64) rate their SWB the same regardless of time; And the elderly (67–95) rated past SWB higher than the present and their future SWB much lower. There were no differences between Anglophones or Francophones. Further analysis revealed the disturbing finding that the oldest participants rated their current SWB significantly lower than the other two age groups. In the second half of our study we found that by simply asking Francophones and Anglophones to rate their SWB in the future – first unspecified as to location, and then in a future ‘if they stay in Quebec’ – produced different response patterns. Both future SWB ratings were the same for Francophones, indicating that the questions were simply redundant. The Anglophones, on the other hand, rated their future SWB in Quebec consistently lower than an unspecified future.

Access to health care services: East-End Montreal (Quebec) English-speaking elderly experience [master's thesis, McGill University] - Thomas, Rosemary Hellen. (2008)

La santé et les minorités linguistiques : l’approche canadienne au regard de cas internationaux - Traisnel, Christophe; Forgues, Éric (Francophonies d'Amérique, 2009)
Dans notre article, nous présentons une analyse comparative de l’approche canadienne de l’enjeu de la santé pour les communautés francophones en situation minoritaire (CFSM). Nous montrons que l’État canadien a favorisé une démarche de concertation avec les acteurs communautaires. Notre analyse comparative nous a permis de dégager une typologie des politiques linguistiques en matière de santé destinées aux CFSM. Cette typologie permet de situer l’expérience canadienne par rapport à d’autres expériences, parfois proches, mais présentant des perspectives différentes, comme le montrent les cas finlandais, belge et états-unien. La « voie » canadienne paraît originale dans la mesure où elle semble se situer entre un modèle communautaire, à l’instar des pays européens, et un modèle individualisé, à l’instar de ce qui se fait aux États-Unis.

Social networks and self-rated health in two French-speaking Canadian community dwelling populations over 65 - Zunzunegui, Maria Victoria; Koné, A.; Johri, Mira; Béland, François; Wolfson, Christina; Bergman, Howard (Social Science & Medicine, 2004)
The objective was to evaluate the associations between older persons’ health status and their social integration and social networks (family, children, friends and community), in two French-speaking, Canadian community dwelling populations aged 65 years and over, using the conceptual framework proposed by Berkman and Thomas. Data were taken from two 1995 surveys conducted in the city of Moncton (n=1518) and the Montreal neighbourhood of Hochelaga-Maisonneuve (n=1500). Social engagement (a cumulative index of social activities), networks consisting of friends, family and children and social support were measured using validated scales. Multiple logistic regressions based on structured inclusion of potentially mediating variables were fitted to estimate the associations between health status and social networks. Self-rated health was better for those with a high level of social integration and a strong network of friends in both locations. In addition, in Hochelaga-Maisonneuve family and children networks were positively associated with good health, though the effect of friend networks was attenuated in the presence of disability, good social support from children was associated with good health. Age, sex and education were included as antecedent variables; smoking, alcohol consumption, exercise, locus of control and depressive symptoms were considered intermediary variables between social networks and health. In conclusion, social networks, integration and support demonstrated unique positive associations with health. The nature of these associations may vary between populations and cultures.